INTERIOR DESIGN OF TASHKENT METRO, FEATURES OF ITS ARCHITECTURE AND CONSTRUCTION - Makhmudova, Malika; Makhmudova, Muhayyo (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The article considers the establishment of the Tashkent metro, its creation, the history of development and design of metro stations, original design solutions of the metro construction technology. The design and artistic solution of the metro stations and its themes are presented mainly on the examples of Tashkent metro stations; information about architects, artists, creators of the architectural and artistic image of the Uzbekistan metro is also presented in the article. The study will allow to get acquainted with the experience of designing and construction of the metro in Uzbekistan and in other countries, and to use it rationally in the construction of the new metro stations.